A method for noise attenuation of straightness measurement based on laser collimation. (September 2021) - Liu, Wenzheng; Zhang, Cong; Duan, Fajie; Fu, Xiao; Bao, Ruijia; Yan, Ming
Highlights: A method for noise attenuation of straightness measurement is proposed. The multi-phase screen is used to simulate the beam propagation in turbulence. The turbulence shield with movable and simple structure is easy to be installed. The turbulence shield effectively improves the accuracy of straightness measurement. Abstract: The accuracy and stability of the straightness measurement based on laser collimation are severely affected by atmospheric turbulence, especially at long working distances. To address this problem, a method for noise attenuation of straightness measurement based on laser collimation is proposed in this paper. The turbulence shield was designed to reduce intensity of atmospheric turbulence on the beam path and weaken its impact on the straightness measurement. Subsequently, the effectiveness of the turbulence shield was simulated by the method of multi-phase screen. To verify the simulation results, the straightness measurement experiment was carried out on the laser five-degree-of-freedom (5-DOF) measurement system. The experimental results showed that the standard deviations of horizontal and vertical straightness noise were reduced by 95.6% and 87.4%, respectively. The experimental results were basically consistent with the simulation results. The turbulence shield effectively improved the accuracy and stability of straightness measurement based on laser collimation.